A COMPARATIVE STUDY OF E-RECRUITMENT EFFECTIVENESS: TIME AND COST EFFICIENCY ANALYSIS AT PT CIPTA MULIA ADINUGRAHA - Asep Dony Suhendra; Supriatin (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The purpose of this study focuses on a comparative analysis of the effectiveness of online recruitment (e-recruitment) implementation at PT Cipta Mulia Adinugraha (CMA) by comparing the key metrics of Time-to-Hire (TTH) and Cost-per-Hire (CPH) between conventional and online recruitment periods. The secondary objective is to identify the impact of digital implementation on Quality of Hire. This research method uses a quantitative-comparative design with a case study approach. Quantitative data were collected from the Human Resources (HRD) Division reports of PT CMA during two one-year observation periods. Efficiency data were analyzed descriptively using comparative percentage change calculations. Qualitative data, derived from in-depth interviews with Talent Acquisition Managers and Staff, were used to strengthen the interpretation of the results. The results show a substantial increase in efficiency. The average TTH decreased by 42% (from 50 days to 29 days), while CPH was saved by an average of 35% (from Rp 5,000,000 to Rp 3,250,000). However, the surge in applicant volume post-digitalization poses new challenges related to mismatch ratios and has the potential to impact Quality of Hire if the in-depth screening process is not optimized. PT.CMA is recommended to balance the efficiencies achieved by integrating Artificial Intelligence (AI) features into its Applicant Tracking System (ATS) to improve competency screening accuracy, thereby achieving overall recruitment effectiveness.